422 Safety and Efficacy of Responsive Neurostimulation for the Treatment of Medically Refractory Epilepsy: A 5-Year Follow-Up Study. (1st April 2022) - Roa, Jorge A.; Feng, Rui; Schupper, Alexander J.; Fields, Madeline; Marcuse, Lara; Germano, Isabelle M.; Bederson, Joshua B.; Ghatan, Saadi; Panov, Fedor
Abstract : INTRODUCTION: Despite antiepileptic drugs (AEDs), >30% of patients with epilepsy continue to have seizures. Responsive Neurostimulation (RNS) provides a nondestructive treatment option for patients with drug-resistant epilepsy (DRE). To date, the safety and efficacy of RNS have not been fully studied due to the lack of prospective data. METHODS: We performed a retrospective analysis of prospectively collected data of DRE patients who underwent RNS implantation between September 2015-December 2020 at our Institution. Patients were followed postoperatively to evaluate seizure-freedom and complications. For each patient, response to RNS was determined as an overall percentage based on the relative reduction in seizure duration/severity, medication requirements and post-ictal state. RESULTS: A total of 103 patients underwent RNS placement. Seven patients developed infections: three required partial salvaging of the system, and only two (1.9%) required complete removal of the RNS device. Six (5.8%) patients experienced small asymptomatic post-operative hemorrhages; none required re-intervention. No cases of stroke or device malfunction/migration were seen. The average follow-up period was 20±13.6 months. Of 74 patients with = 6-month follow-up available, 15 (20.3%) became seizure-free, 18 (24.3%) achieved 75-99% control of seizures, 19 (25.7%) achieved 50-74%, 15 (20.3%) achieved 25-49% and 7 (9.5%) achieved <25% success. Patients with seizures originated in the mesial temporal lobe had a tendency to achieve =75% seizure control (OR = 1.4, P = 0.056). Variables associated with worse outcome (<25% seizure control) included: younger age at epilepsy onset (OR = 2.4, P = 0.043), syndromic etiology (OR = 3.6, P = 0.041), prior no response to =5 AEDs (OR 4.3, P = 0.026) and prior surgical intervention (OR = 1.8, P = 0.052). CONCLUSION: RNS achieved = 50% seizure control in ∼70% of patients. Infections and tract-hemorrhages are the most common complications, but rarely require re-intervention. Seizure-freedom after RNS implantation may be significantly lower in patients affected by aggressive epileptogenic syndromes since a young age, and those who have failed to respond to >5 drugs and prior surgical interventions.